Ivermectin effects in cultured endothelial cells from porcine corpus luteum - Giuseppina Basini; Melissa Berni; Laura Mazzera; Martina Tambassi; Simona Bussolati; Fausto Quintavalla; Simone Bertini; Alicia Maria Carrillo Heredero; Francesca Grasselli (Environmental Toxicology and Pharmacology, 2026)

Polystyrene nanoplastics alone and in mixture with caffeine induced increased swimming behavior of adult Daphnia magna - Sarah Schweickart; Esteban Maroto Hernández; Oscar Rojas Carrillo; Keilor Rojas-Jimenez; José J. Saavedra-Arias; Maria Arias-Andres (Ecotoxicology, 2026)

Breaking barriers: Implementation of a tuberculosis preventive treatment protocol among newly eligible populations with promising results - Paloma Gijón; Teresa Aldámiz; Ana Isabel Ramos-Lisbona; Flor Valenzuela; Cristina Rincón; Raquel Carrillo; Patricia Muñoz; Maria Jesus Ruiz-Serrano (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Post-embryonic consequences of embryonic exposure: Mechanisms of Developmental Toxicity Induced by selective serotonin re-uptake inhibitors and tributyltin in Daphnia magna - Maria Paula Carrillo; Hugo Moro; Benjamín Piña; Maria Vila-Costa; Carlos Barata (Environmental Pollution, 2026)

Copepod-associated microbiome responses to organophosphate ester plasticizers and other bioaccumulative organic pollutants in the ocean - Maria Paula Carrillo; Naiara Berrojalbiz; Claudia Sánz; Jon Iriarte; Núria Trilla-Prieto; Albert Calbet; Enric Saiz; Carlos Barata; Jordi Dachs; Maria Vila-Costa (Water Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Adjuvant-enhanced acaricidal solutions to overcome foliar hydrophobicity for controlling the litchi erinose mite (Aceria litchii) - Wèssèou Estelle Omoboni Germaine Dimon; Daniel Carrillo; Marcelo da Costa Ferreira; Jaqueline Franciosi Della Vechia; Maria Thalia Lacerda Siqueira; Daniel Júnior de Andrade (Experimental and Applied Acarology, 2026)
Litchi erinose mite ( Aceria litchii ) is the primary pest of litchi trees in several countries, causing yield losses of up to 80%. Mite infestations lead to the formation of a protective layer on leaves, known as erinose, which shields mites from various adverse factors, including contact with applied acaricides. This study aimed to evaluate the effect of adjuvants on the properties of acaricide solutions and their impact on A. litchii . Nine adjuvants (Aureo ® , Break-Thru ® , Fighter ® , Fixer ® , Iharaguen-S ® , MSO Spray ® , Orix AD ® , Silwet L-77 ® , and Wetcit Gold ® ) and two acaricides [Sanmite ® (pyridaben) and Ortus ® (fenpyroximate)] were selected for investigation. Initially, key solution properties—surface tension, contact angle, and pH—were measured using a tensiometer for sprays containing acaricides alone and in mixture with adjuvants. Biological efficacy was evaluated in laboratory leaf-disc arenas sprayed with a Potter spray tower, with mite survival assessed 96 h after application. Among the tested acaricides, pyridaben was the most effective, resulting in fewer mites surviving and leaving the erineum. Additionally, the adjuvants Break-Thru ® , Fighter ® , Iharaguen-S ® , Silwet L-77 ® , and Wetcit Gold ® enhanced acaricide efficacy, particularly when combined with pyridaben.

Symmetry breaking induces polarized bandgaps and anomalous elastic wave behavior in gyroid lattices - Maria Carrillo-Munoz; Anwaruddin Siddiqui Mohammed; Bhisham Sharma (Wave Motion, 2026)

Erratum to “Extremely low-frequency magnetic fields (ELF-MF) and radiofrequency: Risk of childhood CNS tumors in a city with elevated ELF-MF exposure” [Environ. Res. Volume 286, Part 2, 1 December 2025, 122858] - Víctor Correa‐Correa; Juan Carlos Núñez‐Enríquez; Gabor Mezei; Roberto Rivera‐Luna; José Gabriel Peñaloza‐González; Salvador Daniel Rivas-Carrillo; Cuauhtémoc Gil Ortiz-Mejía; Claudia Flores-Robles; Erick Velasco-Ramírez; Mario Alexis del Real-Gallegos; Janet Flores‐Lujano; Fernanda Valeria Flores-Pérez; et al. (Environmental Research, 2025)

Extremely low-frequency magnetic fields (ELF-MF) and radiofrequency: Risk of childhood CNS tumors in a city with elevated ELF-MF exposure - Víctor Correa‐Correa; Juan Carlos Núñez‐Enríquez; Gabor Mezei; Roberto Rivera‐Luna; José Gabriel Peñaloza‐González; Salvador Daniel Rivas-Carrillo; Cuauhtémoc Gil Ortiz-Mejía; Claudia Flores-Robles; Erick Velasco-Ramírez; Mario Alexis del Real-Gallegos; Janet Flores‐Lujano; Fernanda Valeria Flores-Pérez; et al. (Environmental Research, 2025)

Caffeine has low affinity for polystyrene micro- and nanoplastics in aquatic environments (and vice versa) - Sarah Schweickart; Esteban Maroto Hernández; Oscar Rojas Carrillo; Keilor Rojas-Jiménez; Maria Arias-Andres (Environmental Pollution, 2025)

Micro-bioplastic impact on gut microbiome, cephalic transcription and cognitive function in the aquatic invertebrate Daphnia magna - María Paula Carrillo; Maria Vila-Costa; Carlos Barata (Environmental Pollution, 2025)

Quantification of the extracellular vesicles and progesterone levels in boar sperm commercial AI doses - Manuel Álvarez-Rodríguez; Alejandro Vicente-Carrillo; Nerea Gala; Maria José Martinez-Alborcia; Helena Nieto-Cristobal; Eduardo de Mercado (Animal Reproduction Science, 2025)

Cortical volumetry and longitudinal cognitive changes in Parkinson’s disease: insights from the COPPADIS cohort - Tania Álvarez-Avellón; Carmen Solares; Juan Álvarez-Carriles; Pablo Franco-Rosado; Patricia Diaz-Galvan; Diego Santos-García; Pablo Mir; Manuel Menéndez-González; Astrid Adarmes Daniela; Almeria Marta; Maria Gema Alonso Losada; Araceli Alonso Cánovas; et al. (Brain Imaging and Behavior, 2025)
Cognitive decline is a major non-motor symptom in Parkinson’s disease (PD), often linked to brain atrophy. This study examines the relationship between cortical atrophy and age groups in predicting cognitive decline in PD over five years. 188 PD patients from the COPPADIS cohort were stratified by age: young (30–55 years, N = 47), middle-aged (56–65 years, N = 59), and older adults (66–75 years, N = 82). Baseline cortical volume was assessed using T1-weighted MRI, and cognitive decline was evaluated using the annual rate of change of the Parkinson’s Disease-Cognitive Rating Scale (PD-CRS). Parametric or non-parametric tests were applied to evaluate group differences. Main analyses consist of several multiple regression analyses to examine associations between baseline brain atrophy and cognitive decline by age group. Older adults exhibited significantly greater cognitive decline in comparison to the younger age groups in the three compose scores of the PDCRS -Fronto-subcortical (H(2) = 41.08, p < 0.001), Posterior Cortical (H(2) = 22.03, p < 0.001), and Total(H(2) = 41.13, p < 0.001). Higher educational level has a significant positive effect on older adults, specifically for working memory performance, delayed verbal memory and the fronto-subcortical composed score. Multiple regression models underscored the predictive value of the bilateral hippocampus, bilateral medial orbitofrontal cortex, right precuneus, and right isthmus cingulate gyrus, together with being an older adult or having a higher education. MRI measures, age, and education predict cognitive decline in PD. Longitudinal assessments are essential for refining atrophy-cognition correlations and optimizing patient stratification.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Leaching potential of heavy metals and metalloids in mining-impacted soils of central Mexico: Accelerated column tests and geochemical modeling - Luisa Fernanda Rueda-Garzón; Alejandro Carrillo-Chávez; Raúl Miranda-Avilés; Maria Jesús Puy Alquiza; Gabriela Zanor; Margarita Ramírez-Ramírez; Carolina Muñoz-Torres; Pooja Kshirsagar; Yanmei Li; Xu Liao; Daniela Kristell Calvo-Ramos (Journal of South American Earth Sciences, 2025)

Enhancing starch levels, granule size and phosphate content in Chlamydomonas reinhardtii through overexpression of ChlreSEX4 - Florencia Torresi; Julieta B. Carrillo; Diego F. Gomez-Casati; Maria V. Busi; Mariana Martín (Plant Science, 2025)

Molecular mechanisms that regulate scopolamine effects on inducible fish antipredation responses in Daphnia magna - María Paula Carrillo; Benjamín Piña; Maria Vila-Costa; Carlos Barata (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Substrate availability may limit the response of tropical bacterioplankton biomass to warming - Xosé Anxelu G. Morán; Maria Ll. Calleja; Federico Baltar; Luis Silva; Mohd Ikram Ansari; Paloma Carrillo de Albornoz; Carlos M. Duarte; Christian Lønborg (Limnology and Oceanography, 2024)
The response of heterotrophic bacterioplankton to the addition of macrophytic dissolved organic matter (DOM) and temperature was investigated in the Red Sea. We added 40 μ mol C L −1 of leachates obtained from seagrass and mangrove leaves to natural bacterial communities, incubated them at three temperatures (25.5°C found in situ plus 3°C below and above that value) and monitored the microbial and biogeochemical responses over 4 d. Seagrass and mangrove DOM, important allochthonous sources in tropical oligotrophic regions, had distinct chemical characteristics compared to unamended seawater, with mangrove substrates containing comparatively more nitrogen and protein‐like fluorescent DOM than seagrass. Specific growth rates ( μ ) increased twofold in the seagrass and mangrove treatments (1.0 and 0.8 d −1 , respectively) relative to the seawater control (0.4 d −1 ). The biomass of heterotrophic bacteria generally reflected μ changes, reaching maximum values of 16.8 and 17.3 μ g C L −1 in the seagrass and mangrove treatments, respectively, compared to just 2.6 μ g C L −1 in seawater. The increase in μ values due to experimental warming followed the metabolic theory of ecology, mostly because of enhanced exoenzymatic activity, while cell size decreased as predicted by the temperature–size rule (mean −3% per °C increase). Although the labile nature of the specific seagrass and mangrove DOM leachates was clearly demonstrated, we conclude that tropical heterotrophic bacteria may have limited capability to increase their biomass as a consequence of future warming, even in the presence of high loadings of macrophytic DOM.

Quantitative determination of tetracyclines in medicated feed for food-producing animals by HPLC–DAD - Elena Butovskaya; Alicia Maria Carrillo Heredero; Giulia Segato; Elena Faggionato; Marialuisa Borgia; Daniela Marchis; Simonetta Menotta; Simone Bertini (Food Additives & Contaminants: Part A, 2024)

Antifeedant activity of guayule resin and its compounds against the agricultural pest Labidostomis lusitanica - Guayente Latorre; Pedro José García-Cano; Sara Rodrigo-Gomez; Enrique Fernández-Carrillo; Maria Engracia Carrión; M. Mercedes García-Martínez; Amaya Zalacain; Gonzalo Ortiz de Elguea-Culebras; Manuel Carmona (Crop Protection, 2024)

Influence of temperature on the population size of Aceria litchii (Acari: Eriophyidae) and the development of its galls - Livia Maria Silva Ataide; Jaqueline F. Della Vechia; Ronald Ochoa; Daniel Carrillo; Alexandra M. Revynthi (Experimental and Applied Acarology, 2024)

Impact of the antibiotic doxycycline on the D. magna reproduction, associated microbiome and antibiotic resistance genes in treated wastewater conditions - Maria Paula Carrillo; Marina Sevilla; Marta Casado; Benjamin Piña; Edward Pastor López; Victor Matamoros; Maria Vila-Costa; Carlos Barata (Environmental Pollution, 2023)

Xeno-estrogenic activity of real-life mixtures of perfluoroalkylated substances in human placenta homogenates - Maria Wielsøe; Jose-Manuel Molina-Molina; Andrea Rodríguez-Carrillo; Vicente Mustieles; Nicolas Olea; Mariana F. Fernandez; Eva Cecilie Bonefeld-Jørgensen (Reproductive Toxicology, 2023)

Bats (Mammalia: Chiroptera) in urban–rural interfaces: community structure associated with pathogen screening in São Paulo—the largest metropolitan region in Brazil - João Eduardo Cavalcanti Brito; Beatriz Gagete Veríssimo de Mello; Natália Carrillo Gaeta; Juliana Maria Nunes Batista; Tiago Roberto Brito; Washington Carlos Agostinho; Paulo Eduardo Brandão; Marcos Bryan Heinemann; Ricardo Augusto Dias (Veterinary Research Communications, 2023)

PM2.5-bound trace metals in an urban area of Northern Mexico during the COVID-19 pandemic: characterization, sources, and health risk - Stephanie Martínez Morales; Julia Griselda Cerón Bretón; Noel Carbajal; Rosa Maria Cerón Bretón; Reyna Lara Severino; Jonathan D.W. Kahl; Jair Rafael Carrillo Ávila; Simón Eduardo Carranco Lozada; Alberto Espinosa Guzmán; Ildefonso Esteban Pech Pech; Rocío Garcia Martinez; Juan Carlos Robles Heredia; et al. (Air Quality, Atmosphere & Health, 2023)

Implementation of effect biomarkers in human biomonitoring studies: A systematic approach synergizing toxicological and epidemiological knowledge - Andrea Rodríguez-Carrillo; Vicente Mustieles; Elena Salamanca-Fernández; Alicia Olivas-Martínez; Beatriz Suárez; Lola Bajard; Kirsten Baken; Ludek Blaha; Eva Cecilie Bonefeld-Jørgensen; Stephan Couderq; Shereen Cynthia D'Cruz; Jean-Baptiste Fini; et al. (International Journal of Hygiene and Environmental Health, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Optimization of gonadotropin stimulation protocols for in vitro embryo production in prepubertal Mediterranean water buffalo - Luke Currin; Hernan Baldassarre; Mariana Priotto de Macedo; Werner Giehl Glanzner; Karina Gutierrez; Katerina Lazaris; Zigomar da Silva; Vanessa Guay; Maria Elena Carrillo Herrera; Caitlin Brown; Erin Joron; Ron Herron; et al. (Theriogenology, 2023)

Triclosan is a KCNQ3 potassium channel activator - Victor De la Rosa; Maria Luisa Guzmán-Hernández; Elisa Carrillo (Pflügers Archiv - European Journal of Physiology, 2022)

Salt intake and gastric cancer: a pooled analysis within the Stomach cancer Pooling (StoP) Project - Samantha Morais; Adriana Costa; Gabriela Albuquerque; Natália Araújo; Claudio Pelucchi; Charles S. Rabkin; Linda M. Liao; Rashmi Sinha; Zuo-Feng Zhang; Jinfu Hu; Kenneth C. Johnson; Domenico Palli; et al. (Cancer Causes & Control, 2022)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Implications of asymptomatic infection for the natural history of selected parasitic tropical diseases - Jorge Alvar; Fabiana Alves; Bruno Bucheton; Louise Burrows; Philippe Büscher; Eugenia Carrillo; Ingrid Felger; Marc P. Hübner; Javier Moreno; Maria-Jesus Pinazo; Isabela Ribeiro; Sergio Sosa-Estani; et al. (Seminars in Immunopathology, 2020)
Progress has been made in the control or elimination of tropical diseases, with a significant reduction of incidence. However, there is a risk of re-emergence if the factors fueling transmission are not dealt with. Although it is essential to understand these underlying factors for each disease, asymptomatic carriers are a common element that may promote resurgence; their impact in terms of proportion in the population and role in transmission needs to be determined. In this paper, we review the current evidence on whether or not to treat asymptomatic carriers given the relevance of their role in the transmission of a specific disease, the efficacy and toxicity of existing drugs, the Public Health interest, and the benefit at an individual level, for example, in Chagas disease, to prevent irreversible organ damage. In the absence of other control tools such as vaccines, there is a need for safer drugs with good risk/benefit profiles in order to change the paradigm so that it addresses the complete infectious process beyond manifest disease to include treatment of non-symptomatic infected persons.

Inhibition of TLR4 attenuates vascular dysfunction and oxidative stress in diabetic rats - Maria Alicia Carrillo-Sepulveda; Kathryn Spitler; Deepesh Pandey; Dan E. Berkowitz; Takayuki Matsumoto (Journal of Molecular Medicine, 2015)

Erratum to: Activation of Toll-like receptor 3 increases mouse aortic vascular smooth muscle cell contractility through ERK1/2 pathway - Trevor Hardigan; Kathryn Spitler; Takayuki Matsumoto; Maria Alicia Carrillo-Sepulveda (Pflügers Archiv - European Journal of Physiology, 2015)

Activation of Toll-like receptor 3 increases mouse aortic vascular smooth muscle cell contractility through ERK1/2 pathway - Trevor Hardigan; Kathryn Spitler; Takayuki Matsumoto; Maria Alicia Carrillo-Sepulveda (Pflügers Archiv - European Journal of Physiology, 2015)

Toll-like receptor 2 mediates vascular contraction and activates RhoA signaling in vascular smooth muscle cells from STZ-induced type 1 diabetic rats - Luke Schmidt; Maria Alicia Carrillo-Sepulveda (Pflügers Archiv - European Journal of Physiology, 2015)

A Cannabigerol Quinone Alleviates Neuroinflammation in a Chronic Model of Multiple Sclerosis - Aitor G. Granja; Francisco Carrillo-Salinas; Alberto Pagani; María Gómez-Cañas; Roberto Negri; Carmen Navarrete; Miriam Mecha; Leyre Mestre; Bend L. Fiebich; Irene Cantarero; Marco A. Calzado; Maria L. Bellido; et al. (Journal of Neuroimmune Pharmacology, 2012)

Establishment constraints of an alien and a native conifer in different habitats - Amparo Carrillo-Gavilán; Josep Maria Espelta; Montserrat Vilà (Biological Invasions, 2012)

Does phylogeny matter? Assessing the impact of phylogenetic information in ecological meta‐analysis - Scott A. Chamberlain; Stephen M. Hovick; Christopher J. Dibble; Nick L. Rasmussen; Benjamin G. Van Allen; Brian S. Maitner; Jeffrey R. Ahern; Lukas P. Bell‐Dereske; Christopher L. Roy; Maria Meza‐Lopez; Juli Carrillo; Evan Siemann; et al. (Ecology Letters, 2012)
Meta‐analysis is increasingly used in ecology and evolutionary biology. Yet, in these fields this technique has an important limitation: phylogenetic non‐independence exists among taxa, violating the statistical assumptions underlying traditional meta‐analytic models. Recently, meta‐analytical techniques incorporating phylogenetic information have been developed to address this issue. However, no syntheses have evaluated how often including phylogenetic information changes meta‐analytic results. To address this gap, we built phylogenies for and re‐analysed 30 published meta‐analyses, comparing results for traditional vs. phylogenetic approaches and assessing which characteristics of phylogenies best explained changes in meta‐analytic results and relative model fit. Accounting for phylogeny significantly changed estimates of the overall pooled effect size in 47% of datasets for fixed‐effects analyses and 7% of datasets for random‐effects analyses. Accounting for phylogeny also changed whether those effect sizes were significantly different from zero in 23 and 40% of our datasets (for fixed‐ and random‐effects models, respectively). Across datasets, decreases in pooled effect size magnitudes after incorporating phylogenetic information were associated with larger phylogenies and those with stronger phylogenetic signal. We conclude that incorporating phylogenetic information in ecological meta‐analyses is important, and we provide practical recommendations for doing so.

Development of Aptamer Beacons for Rapid Presumptive Detection of Bacillus Spores - John G. Bruno; Maria P. Carrillo (Journal of Fluorescence, 2012)

DNA Aptamer Beacon Assay for C-Telopeptide and Handheld Fluorometer to Monitor Bone Resorption - John Gordon Bruno; Maria P. Carrillo; Taylor Phillips; Douglas Hanson; Jonathan A. Bohmann (Journal of Fluorescence, 2011)

A Novel Screening Method for Competitive FRET-Aptamers Applied to E. coli Assay Development - John G. Bruno; Maria P. Carrillo; Taylor Phillips; Carrie J. Andrews (Journal of Fluorescence, 2010)

The effect of increased serotonergic neurotransmission on aggression: a critical meta-analytical review of preclinical studies - Maria Carrillo; Lesley A. Ricci; Glen A. Coppersmith; Richard H. Melloni (Psychopharmacology, 2009)

Plastic-Adherent DNA Aptamer-Magnetic Bead and Quantum Dot Sandwich Assay for Campylobacter Detection - John G. Bruno; Taylor Phillips; Maria P. Carrillo; Randy Crowell (Journal of Fluorescence, 2009)

Competitive FRET-Aptamer-Based Detection of Methylphosphonic Acid, a Common Nerve Agent Metabolite - John G. Bruno; Maria P. Carrillo; Taylor Phillips; Neal K. Vail; Douglas Hanson (Journal of Fluorescence, 2008)

Development of DNA aptamers for cytochemical detection of acetylcholine - John G. Bruno; Maria P. Carrillo; Taylor Phillips; Blythe King (In Vitro Cellular & Developmental Biology - Animal, 2008)

Involvement of oxidative stress in the impairment in biliary secretory function induced by intraperitoneal administration of aluminum to rats - Marcela A. Gonzalez; Maria del Lujan Alvarez; Gerardo B. Pisani; Claudio A. Bernal; Marcelo G. Roma; María C. Carrillo (Biological Trace Element Research, 2007)

Fluorescence Assay Based on Aptamer-Quantum Dot Binding to Bacillus thuringiensis Spores - Milada Ikanovic; Walter E. Rudzinski; John G. Bruno; Amity Allman; Maria P. Carrillo; Sulatha Dwarakanath; Suneetha Bhahdigadi; Poornima Rao; Johnathan L. Kiel; Carrie J. Andrews (Journal of Fluorescence, 2007)

Does seston size structure reflect fish-mediated effects on water quality in a degraded semiarid wetland? - David G. Angeler; Salvador Sánchez-Carrillo; Maria A. Rodrigo; Miguel Alvarez-Cobelas; Carmen Rojo (Environmental Monitoring and Assessment, 2007)

Activity and expression of ecto-5′-nucleotidase/CD73 are increased by thyroid hormones in vascular smooth muscle cells - Alessandra S. K. Tamajusuku; Maria Alicia Carrillo-Sepúlveda; Elizandra Braganhol; Márcia R. Wink; João J. F. Sarkis; Maria Luiza M. Barreto-Chaves; Ana Maria O. Battastini (Molecular and Cellular Biochemistry, 2006)

On the Importance of Water Depth, Macrophytes and Fish in Wetland Picocyanobacteria Regulation - David G. Angeler; Salvador Sánchez-Carrillo; Maria A. Rodrigo; Olga Viedma; Miguel Alvarez-Cobelas (Hydrobiologia, 2005)